Welfare, behavior, and housing conditions of pigs, considering the basic attitudes of pig farmers in Germany - Gebert, Julia; Kuhne, Franziska (Frontiers in Animal Science, 2025)
This study examines the relationship between livestock farmers’ attitudes toward their pigs and the pigs’ welfare, housing conditions, and occurrence of behavioral abnormalities and health problems. The existing system of livestock farming in Germany has been the subject of considerable criticism due to the conflict between economic goals and ethical standards. Despite the existence of studies that examine the human-animal relationship with regard to species-appropriate animal husbandry and the welfare of farm animals, the present study focuses on the association of pig farmers’ basic attitudes on the behavior and welfare of pigs and the respective housing conditions. This study aims to investigate the relationship between the basic attitudes of livestock farmers, the behavior of pigs, husbandry conditions, disease incidence, and the relationship between humans and pigs. The underlying hypothesis of the study is that there is a significant correlation between the basic attitude of pig farmers and the behavior of the pigs, the housing conditions, the occurrence of diseases, and human-animal relationships. In order to respond to the research question, a quantitative study was conducted in the form of an anonymous online survey of 485 German pig farmers. The results of the study indicate the presence of three basic attitudes among pig farmers: utilitarian, emotional, and a combination of utilitarianism, naturalism, and moralism. Furthermore, the results indicate that there are statistical correlations between the attitudes of livestock farmers and certain behaviors and the health status of pigs. It was found that pigs kept by livestock farmers with a utilitarian attitude showed significantly more signs of abnormal and defensive behavior and health problems than pigs kept by livestock farmers with an emotional attitude. The results of this study contribute to our understanding of pig welfare by highlighting correlations between behavior, health, human-animal relationships, and housing conditions. In addition, the results could help raise awareness of housing conditions and the relationship between farm animals and humans, and emphasize the importance of pig behavior.